Pengaruh Pendapatan Asli Desa (PADes) dan Belanja Modal Terhadap Kinerja Keuangan Desa Turaloa Timur - Yulita Klaudia Sepe; Stefanus H. Gusti Ma (Ekspektasi: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the effect of Village Original Revenue and Capital Expenditure on the Financial Performance of Turaloa Timur Village. This study uses a qualitative method with a descriptive statistical approach. The data used in this study are the APBDes data of Turaloa Timur, Ngada Regency, for the years 2024 and 2025, obtained from Turaloa Timur Village. The results of the study indicate that PADes has a positive impact on village financial performance, indicating that an increase in PADes can reduce the village’s dependence on central government assistance and enhance fiscal autonomy. Conversely, capital expenditure has a significant negative impact on village financial performance, where large capital expenditure is not balanced by improved financial performance, possibly due to improper allocation of funds, inefficiency in planning and management, and failure to generate significant multiplier effects for the village economy. Therefore, an effective village financial management strategy is needed by optimizing PADes and prioritizing thorough planning in allocating capital expenditure to enhance village autonomy and community well-being.